2013
DOI: 10.1111/jir.12048
|View full text |Cite
|
Sign up to set email alerts
|

Taking each day as it comes: staff experiences of supporting people with Down syndrome and Alzheimer's disease in group homes

Abstract: Staff had only limited understanding of how Alzheimer's disease impacted the adults with Down syndrome, their responses to changes were ad hoc, and they used strategies on a trial and error basis. They were committed to providing care, but at the risk of rejecting input and support. The need for collaboration across disability, and aged and disability care was evident to facilitate aging-in-place and planned care transitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
135
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(141 citation statements)
references
References 26 publications
4
135
0
2
Order By: Relevance
“…The demand for a method to handle problems associated with the ageing of people with intellectual disability (as dementia) we found is widely reflected in studies of experiences of staff in working with adults and older people with intellectual disability (Cleary & Doodey, 2016;Furniss, Loverseed, Lippold, & Dodd, 2012;Iacono et al, 2014;McCarron, McCallion, Fahey-McCarthy, Connaire, & Dunn-Lane, 2010;Perera & Standen, 2014;Watchman, 2014;Wilkinson et al, 2005). Several studies of DCM in nursing home settings reported difficulties similar to ours in fulfilling the DCM-preconditions.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The demand for a method to handle problems associated with the ageing of people with intellectual disability (as dementia) we found is widely reflected in studies of experiences of staff in working with adults and older people with intellectual disability (Cleary & Doodey, 2016;Furniss, Loverseed, Lippold, & Dodd, 2012;Iacono et al, 2014;McCarron, McCallion, Fahey-McCarthy, Connaire, & Dunn-Lane, 2010;Perera & Standen, 2014;Watchman, 2014;Wilkinson et al, 2005). Several studies of DCM in nursing home settings reported difficulties similar to ours in fulfilling the DCM-preconditions.…”
Section: Discussionmentioning
confidence: 94%
“…quality of care SCHAAP et Al. dementia (Cleary & Doodey, 2016;Duggan et al, 1996;Emerson, 2001;Iacono, Bigby, Carling-Jenkins, & Torr, 2014;Myrbakk & von Tetzchner, 2008); they tend to use an ad hoc approach (Iacono et al, 2014;Janicki, 2011;Janicki, McCallion, & Dalton, 2002;Watchman, 2008;Wilkinson, Kerr, & Cunningham, 2005). Therefore, an evidence-based method that provides insights, knowledge and skills for professionals in the care of older residents with intellectual disability and dementia is urgently needed, but not yet available.…”
mentioning
confidence: 99%
“…*** p < 0.001. Carling-Jenkins, & Torr, 2013). This present study provides information of early onset aging conditions will diminish the ADL functioning in people with DS.…”
Section: Discussionmentioning
confidence: 90%
“…Poor knowledge of the presence of pain (Iacono et al, 2014;Wilkinson et al, 2005) or difficulties experienced by a person in their environment with staff unaware of the disabling effect of the environment (Wilkinson et al, 2005) were apparent. Difficulty knowing how best to support individuals with dementia were also evident and the need for training regarding behavioural support, communication and the provision of activities is recognized (Furniss et al, 2012).…”
Section: Staffs Knowledge Of Dementiamentioning
confidence: 97%